The Green Flaneur and the Widi'd Street Paul Guzzardo (Global Journal of Human-Social Science, 2021)
Nothing could have been further from my mind. I thought that I was returning to my home in New York at the end of a long trip abroad. Instead, I was at the beginning of the journey that would end with my mother's death. To be specific, it was the afternoon of March 28, 2004, a Sunday, and I was in Heathrow Airport in London on my way back from the Middle East. .... I began making phone calls -reconnecting with home as has always been my habit once I am through reporting a story. That was when my mother, Susan Sontag, told me that there was a chance that she was ill again. My mother was clearly doing her best to be cheerful. "There may be something wrong," she finally told me after I had gone on at far too great length about what the West Bank had been like. While I had been away, she said, she had gone in for her twice-yearly scans and blood tests -the regular routine that she had been following since her surgery and subsequent chemotherapy for the uterine sarcoma she had been diagnosed with six years earlier. "One of the blood tests they've just run doesn't seem so good," she said, adding that she had already had some further tests done, and asking me if I would come with her the following day to see a specialist who had been recommended to her and who had done some follow-up tests a couple of days earlier. He would have the conclusive results then.